Pengaruh Organizational Citizenship Behavior dan Kecerdasan Sosial di Lingkungan Kerja terhadap Kinerja Pegawai pada Sistem Aplikasi Penilaian Prestasi Kinerja Pegawai - Dewi Kesuma Lanny; M. Rajab Lubis; Sjahril Effendy Pasaribu (Journal of Education, Humaniora and Social Sciences (JEHSS), 2022)
The purpose of this study was to determine the effect of organizational citizenship behavior, social intelligence on employee performance. This research method uses quantitative methods. The population is 115 and the sample is 115 employees with total sampling technique. The results showed that there was a significant effect between organizational citizenship behavior on performance seen from t count > t table with p = 0.000 < 0.025, which was 15.217 > 1.981 with sig 0.000 < 0.025, then there was significant effect of social intelligence on performance seen from the value (t count) of 4.288, with a t table of 1.981. So it can be said that the value of t arithmetic t table and significance 0.000 < 0.025. Then, simultaneously there is a significant effect between organizational citizenship behavior and social intelligence on performance seen from the coefficient value (R²) = 0.947 with p = 0.000 < 0.050, the contribution of organizational citizenship behavior and social intelligence to performance is 94.7%. These results are reinforced by the results of the F test where the calculated F value > F table is 998,377 > 3,077 with a significance of 0.000 < 0.050